The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0961000620962550
|View full text |Cite
|
Sign up to set email alerts
|

Embedded librarians as research partners in South Korea

Abstract: Recently, many articles co-authored by librarians have been published in non-library and information science journals. This may indicate that embedded librarians are actively working as research partners in various fields. However, studies have rarely discussed the roles and experience of embedded librarians and, unlike the USA and European countries, the activities of embedded librarians in Korea are not well reported. This study collected and analysed co-authored articles from Korean faculty and librarians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…The efficient structures and policies that can guide the daily activities of an embedded librarian are other critical factors that, in absentia, can complicate the transition of a librarian from the traditional liaison responsibility into an embedded librarian in the day-to-day activities of researchers. The findings of this study corroborate the results from other scholars, such as Carlson and Kneale (2011) and Shin (2021), that the lack of established approaches, paths, policies and guidelines and technological infrastructure hinder libraries' efficient embedment of librarians into research processes.…”
Section: Challenges Faced By Embedded Librarianssupporting
confidence: 87%
See 2 more Smart Citations
“…The efficient structures and policies that can guide the daily activities of an embedded librarian are other critical factors that, in absentia, can complicate the transition of a librarian from the traditional liaison responsibility into an embedded librarian in the day-to-day activities of researchers. The findings of this study corroborate the results from other scholars, such as Carlson and Kneale (2011) and Shin (2021), that the lack of established approaches, paths, policies and guidelines and technological infrastructure hinder libraries' efficient embedment of librarians into research processes.…”
Section: Challenges Faced By Embedded Librarianssupporting
confidence: 87%
“…The librarian's embedding in the research process is at its infancy stage in Africa (Machimbidza et al ., 2022; Mushi et al ., 2020a, b). There are limited services provided for research profiling, systematic and scoping reviews and research profiling (Shin, 2021). Studies such as Mushi (2021), Mushi et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other competencies such as organization; preservation and sharing of research outputs; developing data preservation policies; creating wikis; generating bibliometric reports are important to the librarians (Brown et al, 2015; Robinson-Garcia and Torres-Salinas, 2011); ability to work in research teams (Kesselman and Watstein, 2009; Shin, 2021); finding sources of funds; accessing funding databases; and project fund application (Auckland, 2012). Apart from that, librarians must be able to provide researchers with advice on research data management and creation of databases (Brown et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They reported that the librarian's role as author-contribution was varied-for instance, search strategy, data curation or reading and approving the final manuscripts. Then, embedded librarians increased over the years, transforming their role as supportive in research projects (Shin, 2021).…”
Section: Collaboration With Researchers: the Embedded Librarian And S...mentioning
confidence: 99%